2021
DOI: 10.1111/bph.15407
|View full text |Cite
|
Sign up to set email alerts
|

KV1.3 channels are novel determinants of macrophage‐dependent endothelial dysfunction in angiotensin II‐induced hypertension in mice

Abstract: Background and Purpose: K V 1.3 channels are expressed in vascular smooth muscle cells (VSMCs), where they contribute to proliferation rather than contraction and participate in vascular remodelling. K V 1.3 channels are also expressed in macrophages, where they assemble with K V 1.5 channels (K V 1.3/K V 1.5), whose activation generates a K V current. In macrophages, the K V 1.3/K V 1.5 ratio is increased by classical activation (M1). Whether these channels are involved in angiotensin II (AngII)-induced vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
1
4
0
2
Order By: Relevance
“…We then used peritoneal macrophages as a model to assess changes in proinflammatory profile with potential impact in vascular function. 30 Peritoneal macrophages from AngII-infused mice exhibited altered electrophysiological properties (ie, augmented K V currents, greater use-dependent decay and an increase in the degree of inactivation together with a faster time constant of inactivation; Figure 4C and 4D; Figure S6), as previously reported for classical activated or (M1) macrophages. 31 AngII also increased the expression of Kcna3 and proinflammatory mediators such as Il1β , Il6 , and Cox2 (Figure 4E) and reduced the expression of the antioxidant enzyme, hemooxygenase 1 ( Hmox-1 ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…We then used peritoneal macrophages as a model to assess changes in proinflammatory profile with potential impact in vascular function. 30 Peritoneal macrophages from AngII-infused mice exhibited altered electrophysiological properties (ie, augmented K V currents, greater use-dependent decay and an increase in the degree of inactivation together with a faster time constant of inactivation; Figure 4C and 4D; Figure S6), as previously reported for classical activated or (M1) macrophages. 31 AngII also increased the expression of Kcna3 and proinflammatory mediators such as Il1β , Il6 , and Cox2 (Figure 4E) and reduced the expression of the antioxidant enzyme, hemooxygenase 1 ( Hmox-1 ).…”
Section: Resultssupporting
confidence: 77%
“…31,47 We have recently described that AngII increases the expression of Kcna3 gene in mice aortic perivascular adipose tissue and peritoneal macrophages where it also upregulates Kv current and M1-like cytokines participating in endothelial dysfunction. 30 Here, we found that both preventive and therapeutic treatment with RvD2 clearly restored electrophysiological properties and decreased the expression of Kcna3 and several M1 cytokines while upregulating M2 markers in peritoneal macrophages, demonstrating widespread effects of RvD2. In agreement, RvD2 addition to activated peritoneal macrophages reduced IL-1β secretion, 48 and human macrophages incubated with RvD2 displayed augmented Cd163 expression.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have shown a close interplay between K + ‐channels and hMF polarization, with specific stoichiometries of the subunits and the resulting currents and membrane potentials. [ 47,48,63–66 ] In fact, K + ‐channels are the most complex class of voltage‐gated ion channels from both a functional and a structural standpoint. KCNA3 encodes the voltage‐gated Kv1.3 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Además, estos monocitos/macrófagos tienen un papel causal en el desarrollo del remodelado vascular y la disfunción endotelial, puesto que diferentes tipos de ratones deficientes en macrófagos (98,(198)(199)(200) están protegidos frente al desarrollo del remodelado vascular, la disfunción endotelial y la hipertensión. Además, recientemente hemos publicado que los medios condicionados de macrófagos de ratones infundidos con Ang II inducen la disfunción endotelial a través de la liberación de IL-1b y prostaglandinas derivadas de la COX-2 (201). Los macrófagos tipo M2 también se encontraron dentro de la pared vascular después de la infusión de Ang II (202) y parecen promover la rigidez vascular y el remodelado de la MEC, incluyendo la deposición de colágeno, la fibrosis adventicial y la pérdida de elastina (202), confirmando que los macrófagos tipo M1 o M2 tienen un papel en la disfunción vascular en la hipertensión.…”
Section: Papel De La Inflamación En La Función Y El Remodelado Vascul...unclassified